Analisis Transformasi Pola Kerja Birokrasi dalam Pelayanan Publik Pasca-Pandemi Covid-19 di Kantor Regional I Badan Kepegawaian Negara Yogyakarta - Salsabila, Nadya Nasywa; Darumurti, Awang (UIR PRESS, 2023)
This research is aimed at analyzing the Transformation of Work Patterns of State Civil Servants in Post-Pandemic Public Services as a Response to Changes in Community Behavior in the Regional Office I of the Yogyakarta State Civil Service Agency. This study used qualitative research methods. The results of this research show that the indicators of the transformation of ASN work patterns in services by Regional Office I of the Yogyakarta State Civil Service Agency (BKN) are still not going well overall.Agile capabilities which is owned by Regional Office I of the Yogyakarta State Civil Service Agency (BKN) must continue to be pursued. Leaders who are an influential factor in the performance of the State Civil Apparatus (ASN) should be more open to information technology. Then there needs to be more specific training regarding adaptive responses to changes determined by the center.